Liver anatomy and detoxification function (Henry Stewart Talks, 2026)
Liver anatomy and divisions, Liver microscopic organization, Blood supply and biliary system, Detoxification and enzymes, Nutrient metabolism and protein synthesis, Major liver disorders and impact